Association between right atrial area measured by echocardiography and prognosis among pulmonary arterial hypertension: a systematic review and meta-analysis - Ke Liu; Chunhua Zhang; Bingyu Chen; Mingfeng Li; Peican Zhang (BMJ Open)
Objective The purpose of this meta-analysis was to evaluate the association between enlarged right atrial area (RAA), as measured by echocardiography, and prognosis of patients with pulmonary arterial hypertension (PAH).Design Systematic review and meta-analysis.Data sources To identify potential publications, a comprehensive literature search through MEDLINE, the Cochrane database and the Embase database was performed up to December 2019.Eligibility criteria for selecting studies Studies were included if they reported Cox regression based-HRs with 95% CIs for all-cause mortality or composite endpoint consisting of death and PAH-related events for echocardiography measurements of the RAA or the right atrial area index (RAAI) in patients with PAH.Data extraction and synthesis The unadjusted HR with 95% CI was extracted for the final pooled analysis. A random-effects model was used to determine the value of RAA/RAAI in the prognosis of patients with PAH. The data heterogeneity among the studies was estimated by the I2 statistic and the Cochran Q-statistic.Results Twelve studies with a total of 1085 patients with PAH were finally included in the meta-analysis. These studies had a mean follow-up time ranging from 9.2 months to 5.0 years. Their findings showed that patients with PAH with enlarged RAA/RAAI were associated with poor prognosis. The risk of all-cause mortality in patients with PAH was found to statistically increase by 50% for every 5-unit increase in RAA/RAAI (HR 1.50, 95% CI 1.28 to 1.75, p<0.001). Similarly, the risk of the composite endpoint also significantly increased by 53% for every 5-unit increase in RAA/RAAI (HR 1.53, 95% CI 1.23 to 1.89, p<0.001). Subgroup analyses in which the patients were stratified by RAA and RAAI were consistent with the main results.Conclusion The meta-analysis suggested that enlarged RAA/RAAI were associated with increased risk of poor prognosis in patients with PAH.